Enhancing Teacher Performance Through Coaching: A Study on Differentiated Learning in Primary Schools - Nuti Handayani; Hizir Sofyan; Niswanto Niswanto (Heca Sentra Analitika, 2026)
This study examines the role of teacher coaching programs in enhancing the effectiveness of differentiated learning in primary schools, focusing on SD Negeri Langgo and SD Negeri 2 Peukan Pidie. Using a qualitative research approach with a descriptive method, the study explores how structured teacher coaching influences instructional strategies, teacher competence, and student learning outcomes. Data were collected through semi-structured interviews, classroom observations, and document analysis, followed by thematic analysis. The findings indicate that teacher coaching programs significantly improved instructional quality, although the coaching approaches varied between schools. SD Negeri Langgo implemented individual mentoring, while SD Negeri 2 Peukan Pidie emphasized peer discussions and collaborative learning communities. Both approaches helped teachers adapt their teaching methods to better support students with diverse learning needs. However, challenges such as limited professional training, time constraints, resource shortages, and varying student motivation hindered full implementation of differentiated instruction. Despite these challenges, the study found that differentiated learning positively impacted student engagement, literacy, and numeracy skills. Students demonstrated higher levels of participation and improved academic performance following the enhancement of teacher coaching programs. The study highlights the importance of continuous professional development, institutional support, and access to instructional resources to sustain effective differentiated learning practices. The study concludes that teacher coaching is essential in fostering effective differentiated instruction. It recommends expanding teacher training programs, providing better resource allocation, and integrating motivation-enhancing strategies to improve student learning experiences. Future research should explore long-term effects of differentiated learning and strategies for enhancing student motivation in diverse classrooms